Tonic Pupil Following Pars Plana Vitrectomy and Endolaser - Benyamin Ebrahim; Larry Frohman; Marco Zarbin; Neelakshi Bhagat (Case Reports in Medicine)
Tonic pupil was observed in a 67 year-old patient following a retinal detachment repair with pars plana vitrectomy, endolaser and silicone oil tamponade performed under retrobulbar anesthesia. The probable location of disturbance is the postganglionic parasympathetic fibers in the short ciliary nerves along their course to the pupil in the suprachoroidal space. A likely explanation for this phenomenon is injury to short ciliary nerves by endolaser treatment.